Potential applications of virtual reality devices in older people. Narrative review - Kujawska, Agnieszka; Prylińska, Monika; Ziółkowska, Sylwia; Husejko, Jakub; Androsiuk-Perkowska, Joanna; Skierkowska, Natalia; Perkowski, Radosław; Gajos, Małgorzata; Topka, Weronika; Szmelcer, Beniamin; et al. (Journal of Education, Health and Sport, 2019)
Introduction Many of the non-pharmacological therapeutic interventions such as physical and mental exercises are focused on some of the dimensions of human cognition only. Therefore, methods involving immersion in VR (VR) might presumably belong to the more effective treatment methods. VR is a rapidly evolving technology, which is successfully and increasingly present in various branches, including medicine. Despite its increasing popularity for many people it is still new and unexplored, which leads to negative opinions and unwillingness to use in geriatric population. Therefore, the main purpose of this article is to describe application of virtual reality and new technologies devices in geriatrics. Material and methods Articles in the EBSCO database were analyzed using keywords: virtual reality, frailty, pain, phobias, stroke rehabilitation, adverse effects. Available literature has been subjectively selected. Results Researches with applications of virtual reality techniques in sarcopenia and frailty, phobias, stroke rehabilitation, pain therapy were described. Moreover, potential adverse effects were discussed. Conclusions An overview of the research results in this area indicates that the virtual reality, possibly could be applied in mental and physical training in the cases of both physiological aging and various disorders. At the same time, the disadvantages and potential adverse effects have been pointed out. Further studies on application of VR in older people should be conducted to determine its effectiveness in various clinical and nonclinical settings.